Twenty-first century Jihad : law, society and military action - Kendall, Elisabeth; Stein, Ewan (London ; I.B. Tauris, 2015)
The term 'jihad' has come to be used as a byword for fanaticism and Islam's allegedly implacable hostility towards the West. But, like other religious and political concepts, jihad has multiple resonances and associations, its meaning shifting over time and from place to place.--
Introduction: Contextualising twenty-first century jihad / Elisabeth Kendall and Ewan Stein -- Prologue: A short history of jihad / Carole Hillenbrand -- Part I. Historical antecedents of contemporary jihad -- 1. Divine authority and territorial entitlement in the Hebrew Bible and the Qur'an / Reuven Firestone -- 2. Early competing views on jihad and martyrdom / Asma Afsaruddin -- 3. Definitions and narratives of martyrdom in Sunni Hadith literature / Roberta Denaro -- 4. The non-military aspects of Kitab al-jihad / Mustafa Baig -- 5. Responses to the Almoravid intervention in al-Andalus / Russell Hopley -- 6. The 'greater' jihad in classical Islam / Gavin Picken -- Part II. Jihad in modern politics and society -- 7. Sectarian violence as jihad / Sami Zubaida -- 8. The new Qa'ida Wahhabists and the revival of jihad in Saudi Arabia / Mansour Alnogaidan -- 9. The Muslim brotherhood and jihad / Hossam Tammam -- 10. Jihad discourse in Egypt under Muhammad Mursi / Ewan Stein -- 11. Jihad as a form of struggle in the resistance to apartheid in South Africa / Na'eem Jeenah -- 12. Women, Islam and war in Lebanon and the Palestinian territories / Maria Holt -- 13. Al-Qa'ida, jihad and the 'surge' / Lt. Gen. Sir Simon Mayall -- Part III. Representations of jihad in modern culture -- 14. Yemen's al-Qa'ida and poetry as a weapon of jihad / Elisabeth Kendall -- 15. Poetics of martyrdom in early modern Palestine / Rana Issa -- 16. Hollywood and jihad / Thomas Riegler -- 17. 'Jihadists of the pen' in Victorian England / Eric Germain -- 18. The appeal of Yusuf al-Qaradawi's interpretation of Jihad? / Sherman Jackson -- 19. What is new about Yusuf al-Qaradawi's jihad? / Sheikh Rachid al-Ghannouchi.
Includes bibliographical references and index.
Keywords: Jihad -- History -- 21st century; Jihad -- Social aspects; War -- Religious aspects -- Islam; Islam and politics; Jihad (heligt krig) -- historia; Islam och politik; Jihad (heligt krig) -- sociala aspekter